Analisis Kinerja Penyelidikan Dan Penyidikan Dalam Menanggulangi Tindak Pidana Kriminal di Polres Karanganyar - Valentino Aquila De Wahyu; Aurelia Eka Junita; Amanda Destiana; Krisna Agus Setyabudi; Farrah Nidau Daini; FX. Hastowo Broto Laksio (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The National Police of the Republic of Indonesia (Polri) is a government institution whose main task is to ensure law enforcement, security and public order, provide services as well as protect and develop. Therefore, the National Police plays an important role in ensuring security and public order and enforcing the law to create peace and justice for all Indonesian people. In every criminal case, criminal investigations must be carried out professionally, transparently and responsibly to uphold the supremacy of law that reflects a sense of justice. (1) (5) The Criminal Procedure Code explains that an investigation is a series of investigative actions used to search for and discover an incident that is suspected of being criminal in order to determine whether an investigation can be carried out according to the Criminal Procedure Code.